Comparative analysis of salivary cytokine profiles in newly diagnosed pediatric patients with cancer and healthy children - Alina Paganini; Nora Fritschi; Cornelia Filippi; Nicole Ritz; Urs Simmen; Katrin Scheinemann; Andreas Filippi; Tamara Diesch-Furlanetto (Scientific Reports)
Abstract Salivary cytokines have the potential to serve as biomarkers for evaluating cancer progression and treatment response in specific cancer types. This study explored salivary cytokine profiles in pediatric cancer patients and healthy controls, examining changes during chemotherapy. We conducted a prospective study involving newly diagnosed cancer patients and healthy controls under 19 years old. Saliva samples were collected at diagnosis, and three and six months post-diagnosis for cancer patients, while healthy controls provided samples at a single time point. Cytokine levels were analyzed using Luminex technology. Our study included 19 cancer patients (10 with leukemia, 5 with lymphoma, and 4 with solid tumors) and 128 healthy controls aged 4 to 18 years. At diagnosis, patients with leukemia and solid tumors showed elevated levels of interferon-γ, interleukin (IL)-1α, IL-1β, IL-4, IL-5, IL-8, IL-10, and tumor necrosis factor. After three months, IL-6, IL-10, and inducible protein-10 levels significantly increased, while IL-1α, IL-1β, and IL-8 rose by six months. These findings indicate that salivary cytokines are elevated at diagnosis and during initial treatment phases in pediatric cancer patients, highlighting saliva’s potential as a noninvasive medium for early detection of systemic diseases in children.